Cutting Properties of Austenitic Stainless Steel by Using Laser Cutting Process without Assist Gas. (2nd October 2012) - Ozaki, Hitoshi; Koike, Yosuke; Kawakami, Hiroshi; Suzuki, Jippei
Abstract : Recently, laser cutting is used in many industries. Generally, in laser cutting of metallic materials, suitable assist gas and its nozzle are needed to remove the molten metal. However, because of the gas nozzle should be set closer to the surface of a workpiece, existence of the nozzle seems to prevent laser cutting from being used flexible. Therefore, the new cutting process, Assist Gas Free laser cutting or AGF laser cutting, has been developed. In this process, the pressure at the bottom side of a workpiece is reduced by a vacuum pump, and the molten metal can be removed by the air flow caused by the pressure difference between both sides of the specimen. In this study, cutting properties of austenitic stainless steel by using AGF laser cutting with 2 kW CO2 laser were investigated. Laser power and cutting speed were varied in order to study the effect of these parameters on cutting properties. As a result, austenitic stainless steel could be cut with dross-free by AGF laser cutting. When laser power was 2.0 kW, cutting speed could be increased up to 100 mm/s, and kerf width at specimen surface was 0.28 mm.